2020
DOI: 10.1007/s42452-020-2535-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nickel-spinal-Ferrites on EMI shielding properties of polystyrene/polyaniline blend

Abstract: Magnetic and electrically conductive polymeric nanocomposites were fabricated using polystyrene (PS) as matrix, Nickel Ferrites (NiFe) as magnetic nanofiller and polyaniline (PANI) as electrically conductive nanofiller. Electromagnetic interference (EMI) shielding and infrared (IR) blocking are the main application of these nanocomposites. PANI and NiFe were successfully prepared by chemical and co-precipitation methods respectively. The successful fabrication of nanofillers was confirmed by the X-ray diffract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Furthermore, Sulaiman et al [ 71 ] reported excellent absorption characteristics of −24.86 dB for Co 0.5 Zn 0.5 Fe 2 O 4 /PANI-PTSA nanocomposites (weight ratio 1:1) with an optimal matching thickness of 3 mm. Total shielding effectiveness, SE T of 35 dB for Polystyrene/PANI/Nickel spinel ferrite composite, is noticed in a broad frequency range of 0.1 to 20 GHz by Shakir et al [ 72 ]. Moreover, Li et al [ 73 ] reported total shielding effectiveness SE T of 48.4 dB with nitrogen-doped reduced graphene oxide/CoFe 2 O 4 hybrid nanocomposites in X and Ku bands.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Sulaiman et al [ 71 ] reported excellent absorption characteristics of −24.86 dB for Co 0.5 Zn 0.5 Fe 2 O 4 /PANI-PTSA nanocomposites (weight ratio 1:1) with an optimal matching thickness of 3 mm. Total shielding effectiveness, SE T of 35 dB for Polystyrene/PANI/Nickel spinel ferrite composite, is noticed in a broad frequency range of 0.1 to 20 GHz by Shakir et al [ 72 ]. Moreover, Li et al [ 73 ] reported total shielding effectiveness SE T of 48.4 dB with nitrogen-doped reduced graphene oxide/CoFe 2 O 4 hybrid nanocomposites in X and Ku bands.…”
Section: Resultsmentioning
confidence: 99%
“…The following equations were used to calculate shielding effectiveness through scattering parameters taken from VNA. 33,4244 …”
Section: Resultsmentioning
confidence: 99%
“…Ferromagnetic materials are excellent nanomaterials for magnetic field shielding at low frequencies [13,14]. EMI shielding at a high-frequency range requires the magnetic field to always be reversed to the original magnetic field produced by the current in excellent conductors [15][16][17][18][19][20][21][22]. This outstanding EMI shielding evaluates the usage of metals as well as magnetic nanomaterials to attenuate electric and magnetic field radiation [23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%